Even God cannot change the past reflections on seventeen years of the European seminar in historical methodology - Grabbe, Lester L. 1945- ([London] Bloomsbury Publishing, 2019)
"This volume represents the final publication of the European Seminar in Historical Methodology. The volume reflects on the ground-breaking work of this prestigious seminar in the field of biblical history. In part one, long-term members of the seminar (Bob Becking, Ehud Ben Zvi, Philip R. Davies, Ernst Axel Knauf, Niels Peter Lemche, Thomas L Thompson) provide reflections on its work. Part two presents an opportunity for readers to benefit from contributions that have remained heretofore unpublished. This includes material on the Persian period, questions of orality and writing, and contributions on the Maccabean period. Bringing these papers together in a published form provides a fitting way to round out the work of this significant endeavour in historical methodology."--Bloomsbury Publishing
Includes bibliographical references and index
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Bible -- History of Biblical events; European seminar in historical methodology; Bible -- Criticism, interpretation, etc; Bible; European seminar in historical methodology; Konferenzschrift